2013
DOI: 10.1186/1475-2840-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum osteoprotegerin with vascular calcification in patients with type 2 diabetes

Abstract: BackgroundOsteoprotegerin is a member of the tumor necrosis factor-related family and inhibits RANK stimulation of osteoclast formation as a soluble decoy receptor. The goal of this study was to determine the relationship of serum osteoprotegerin with vascular calcification in patients with type 2 diabetes.MethodsThe subjects were 124 patients with type 2 diabetes mellitus, including 88 males and 36 females with a mean (± SD) age of 65.6 ± 8.2 years old. Serum levels of osteoprotegerin, osteocalcin, fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…Our results support the results of an earlier study (8) in which increased serum OPG levels were associated with elevated CAC scores in asymptomatic individuals with type 2 diabetes. Our results are in agreement with several other studies that have shown an increase in serum OPG in association with vascular injury assessed by various methods in patients with and without type 2 diabetes (7, 2628). The mechanisms for the increased serum OPG levels are, however, not clear.…”
Section: Discussionsupporting
confidence: 93%
“…Our results support the results of an earlier study (8) in which increased serum OPG levels were associated with elevated CAC scores in asymptomatic individuals with type 2 diabetes. Our results are in agreement with several other studies that have shown an increase in serum OPG in association with vascular injury assessed by various methods in patients with and without type 2 diabetes (7, 2628). The mechanisms for the increased serum OPG levels are, however, not clear.…”
Section: Discussionsupporting
confidence: 93%
“…OPG is produced by osteoblasts as well as by endothelial cells and VSMCs [9]. Its anti-osteoclastic properties argue for a potential role in bone-vascular crosstalk affecting vascular calcification [16] although the exact underlying mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…OPG concentrations in serum from CKD patients were found to be independently associated with the serum potential to induce calcification of smooth muscle cells in vitro [39]. Moreover, serum OPG levels have been independently associated with cervical artery calcification in non-dialysis CKD patients [9] and with moderate coronary artery calcification in patients with type 2 diabetes, with and without diabetic nephropathy [40]. Studies in HD patients demonstrated higher serum OPG levels compared with control subjects [17] and a positive association of OPG with arterial medial calcification assessed by plain film radiography of the pelvis [18], with coronary artery calcification score assessed by CT scan both at baseline and after 1 year [41], as well as with mortality [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoprotegerin (OPG) is a soluble member of the tumor necrosis factor (TNF) receptor superfamily, produced by osteoblasts and vascular endothelial and smooth muscle cells [27]. It has an anti-osteoclastic effect being a soluble decoy receptor for the osteoclast activator RANKL (receptor activator of nuclear factor-κB ligand).…”
Section: Introductionmentioning
confidence: 99%